Temporal factors and distance to human settlement affect nest survival of the endangered Yellow-headed Parrot in Belize, Central America. Issue 2 (25th February 2022) - Tarazona-Tubens, Fabio L; Britt, Charles R; Abadi, Fitsum; Muschamp, Mario; Desmond, Martha J
Abstract: The endangered Yellow-headed Parrot ( Amazona oratrix ) has experienced a considerable reduction in abundance and distribution. Identifying natural and anthropogenic causes of nest failure is a critical step towards developing conservation actions that increase nest survival. In this study, we examined daily nest survival in relation to temporal, habitat, and anthropogenic factors, as well as nest site properties. We monitored nests ( n = 124) across 6 study sites in Belize during 2017 and 2018 and independently modeled the effects of predation, abandonment and poaching on daily nest survival rates. Overall, the estimated cumulative nest survival probability was 0.18 (95% CI: 0.12–0.25). Predation was the main cause of nest failure, followed by abandonment, and poaching. Our results showed that nest predation and abandonment usually occurred early in the nesting cycle. Day within the nesting season negatively influenced daily survival for abandoned nests and had a quadratic effect on survival for poached nests. Poaching events occurred at a specific date range later in the season, with nests farther from the nearest human settlement having higher daily survival. Findings from this study highlight the additive mortality effect that nest poaching is having on Yellow-headed Parrot populations in Belize and show that managers can anticipate the timing and location of nests most vulnerable to poaching. Lay Summary: Yellow-headed Parrots ( Amazona oratrix ) are classified as globally endangered due to population declines attributed to the pet trade and habitat loss, resulting in small remnant populations scattered throughout its historical range. We monitored nests in Belize and identified factors associated with predation, abandonment, and poaching. Predation was the main cause of nest failure, followed by abandonment and poaching. Increasing nest age was associated with lower probability of nest predation and abandonment. Increasing day within the nesting season was associated with increasing abandonment, while poaching occurred within a specific range of days. Increasing distance to human settlements reduced nest poaching. While poaching is a source of additive mortality for Yellow-headed Parrot nests in Belize, managers can anticipate the timing and location of nests vulnerable to poaching. Graphical Abstract: